Status of integrated crop-livestock research in the mixed farming systems of the Global South: a scoping study - Mabhaudhi, Tafadzwanashe; Chibarabada, T. P.; Sikka, Alok (Frontiers Media, 2023)
Mixed farming systems (MFS) are the main food source and exist across almost all agroecological regions in the Global South. A systematic scoping review was conducted to identify the status of integrated crop-livestock research in MFS of the Global South. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol was used to identify 210 studies (excluding reviews) addressing productivity, resilience, challenges, opportunities, and perceptions of integrating crops and livestock in the Global South from the Scopus and Web of Science database. Publication details, problem statement, experimental details and research outcomes of each study were extracted into an MS. Excel sheet. Descriptive methods such as frequency counting and the word frequency cloud were used to analyze the data and identify emerging themes. Integrated crop-livestock research was mostly conducted in sub-Saharan Africa and Asia and not much from North Africa and the Caribbean. The integrated research has been focused on farm production of human food and animal feed by smallholder farmers and soil productivity. Maize was the most dominant crop, while for livestock, it was sheep and cattle. The integrated crop-livestock research seeked to address various challenges, including the growing demand for food and fodder, water scarcity, land scarcity and degradation, climate change, disease outbreaks and social changes. The review summarized proposed strategies and approaches to improve the efficiency of MFS in the Global South. Under the current challenges, feed quality and supply can be improved through adoption of high biomass, climate smart and improved drought-tolerant fodder crops. Using crop residues incorporated in crop fields for improved soil organic matter and controlled grazing were some strategies suggested for land rehabilitation. Building the resilience of smallholder farmers in MFS can be done through diversification and ensuring access to information, markets and finance. Policies that promote the business component, i.e., markets, training, gender equality, private investments, tenure systems and technology adoption were identified for the sustainability of MFS. There is need for research that integrates crop-livestock systems and natural resource management innovations and that evaluates sustainable intensification strategies to meet productivity goals without compromising social and ecological outcomes in MFS.